ANALYSIS OF HUMAN RESOURCES DEVELOPMENT IN JEMBRANA DISTRICT GENERAL ELECTION COMMISSION - Dwipayana, I Putu Eka; Kurnia M, Fakhruddin (Universitas Ichsan Sidenreng Rappang, 2024)
The aim of this research is to find out and describe the implementation of human resource development, obstacles, and efforts to overcome the obstacles faced in implementing human resource development at the KPU Jembrana Regency. The research approach used is descriptive qualitative. The selection of informants used purposive sampling technique. The data analysis technique used is an interactive data analysis technique where data analysis is carried out interactively and continues continuously until completion. The results of the research show that the human resource development that has been carried out by the KPU Jembrana Regency includes: Recruitment of employees who are tailored to their work experience, education and training in accordance with organizational needs, and career development for all members by providing training, transfer and promotion opportunities in accordance with organizational capabilities and needs. Obstacles faced by the Jembrana. Regency KPU in developing human resources include: Lack of employees, not having definite HR standards, costs and time, and communication that is not running well. Efforts made by the KPU Jembarana Regency to overcome existing obstacles in human resource development include: Increasing the quality of productive human resources and their equitable distribution, Prioritizing HR capabilities that are in line with technological advances, Prioritizing HR standards that are in accordance with organizational culture and prioritizing communication and work with the team, and collaborating with the KPU Provincial to provide training and development.